Tracking microRNA Processing Signals by Degradome Sequencing Data Analysis - Yu, Dongliang; Xu, Min; Ito, Hidetaka; Shao, Weishan; Ma, Xiaoxia; Wang, Huizhong; Meng, Yijun (Frontiers in Genetics, 2018)
Degradome sequencing (degradome-seq) was widely used for cleavage site mapping on the microRNA (miRNA) targets. Here, the application value of degradome-seq data in tracking the miRNA processing intermediates was reported. By adopting the parameter "signal/noise" ratio, prominent degradome signals on the miRNA precursors were extracted. For the 15 species analyzed, the processing of many miRNA precursors were supported by the degradome-seq data. We found that the supporting ratio of the "high-confidence" miRNAs annotated in miRBase was much higher than that of the "low-confidence". For a specific species, the percentage of the miRNAs with degradome-supported processing signals was elevated by the increment of degradome sampling diversity. More interestingly, the tissue- or cell line-specific processing patterns of the miRNA precursors partially contributed to the accumulation patterns of the mature miRNAs. In this study, we also provided examples to show the value of the degradome-seq data in miRNA annotation. Based on the distribution of the processing signals, a renewed model was proposed that the stems of the miRNA precursors were diced through a "single-stranded cropping" mode, and "loop-to-base" processing was much more prevalent than previously thought. Together, our results revealed the remarkable capacity of degradome-seq in tracking miRNA processing signals.